Seeking health: the hierarchy of resort in utilisation patterns of traditional and western medicine in multi-cultural Katutura, Namibia - LeBeau, Debie (Rhodes University, Faculty of Humanities, Department of Anthropology, 1999)
This thesis examines health care choices patients make when illness and misfortune occur. Research on health seeking behaviour was conducted in Katutura (the African township outside of Windhoek in Namibia) during 1996 and 1997. Due to the availability of a wide range of health care options from both the western and the traditional medical systems, utilisation of traditional medicine represents a conscious choice by patients and is not due to a lack of other alternatives. The use of traditional medicine can therefore be attributed to social, cultural, and personal factors rather than access, cost, and distance to modern health care facilities. A set of theoretical postulates is constructed to explain health seeking behaviour, including western and African concepts of ill health, which integrates both macro and micro-level analysis. Through macro-level analysis, this model postulates that western and traditional medical systems are able to exist within a single society due to the presence of co-existing ideologies (Medical Systems Theory). This model further postulates that social change is a significant attribute of post-colonial Namibian society (Post-colonial Theory). Rapid social change causes social disequilibrium leading to insecurities within the population which increase traditional health care utilisation, especially due to witchcraft accusation. Thus, macro-level theories are used to explain the existence and form of health care alternatives in Katutura; while micro-level analysis is used to examine how people make rational health care choices based on individualised variables within the enabling and constraining umbrella of Namibia's social structure. These variables include the individual's means, goals, desires, and environment of physical and social objects. Health seeking behaviour is influenced by the individual's previous experiences (history), personal constraints, and access to information. Based on data from the 1996 Tradition and Health Survey administered as part of the research for this dissertation, a model for health seeking behaviour is developed to guide the analysis of qualitative data. This model postulates that different patterns of utilisation depend on perceived causes, reasons and origins (aetiology) as well as manifestations of illness. Some illnesses are perceived of as clearly African and some are seen to be clearly western (both of these perceptions result in a single utilisation pattern). Some illnesses have a social/spiritual aetiology but universally recognised manifestations (resulting in a simultaneous utilisation pattern), and some illnesses are of indeterminate aetiology until treatment begins (resulting in a multi-faceted utilisation pattern). In addition to a utilisation pattern based on the aetiology and manifestation of illness, previous health seeking experiences influence, to a certain extent, subsequent health care choices; whereby the failure of one medical system to produce satisfactory results can cause health seekers to shift to another treatment regimen. In Katutura choices patients make are also influenced, to a certain extent, by the urban nature of the health seeking environment. Urban patients seek traditional medicine for a range of social/spiritual aetiologies, due to rapid social change and the experience of new and threatening situations. Urban patients also have more knowledge and experience with the western concept of contagious transmission as opposed to the traditional concept of social/spiritual contamination. In addition, health seeking patterns vary slightly between the different ethnic groups in Katutura. Traditional aetiological beliefs of the different ethnic groups in Katutura are reflected in current cultural beliefs about the cause of illness.
Keywords: Traditional medicine -- Namibia -- Katutura (Windhoek); Social medicine -- Namibia -- History; Traditional medicine -- Social aspects -- Namibia -- History; Medical anthropology -- Namibia